Association Between Antihypertensive Medication Adherence and Quality of Life in Hypertensive Patients - Hutagaol, Sherly H.; Sibagariang, Ayu; Pardosi, Naomi (Indonesian Journal of Science and Pharmacy, 2026)
Hypertension is a chronic non-communicable disease known as a “silent killer” that can reduce patients’ quality of life if not properly managed. Medication adherence is a key determinant of therapeutic success and prevention of complications. This study aimed to analyze the relationship between adherence to antihypertensive medication and quality of life among hypertensive patients at Porsea Regional General Hospital. This study used a quantitative observational design with a cross-sectional approach. A total of 57 hypertensive patients were selected using accidental sampling. Medication adherence was measured using the MMAS-8 questionnaire, while quality of life was assessed using WHOQOL. Data were analyzed using the Spearman correlation test. The results showed that 35.1% of respondents had high adherence, while most respondents had moderate quality of life. Statistical analysis indicated that there was no significant relationship between medication adherence and quality of life (Sig. = 0.049; p > 0.05). In conclusion, adherence to antihypertensive medication was significantly associated with quality of life in this population. However, improving adherence remains important to prevent complications and optimize patient outcomes.